การถ่ายทอดภูมิปัญญาท้องถิ่นเรื่อง "เมี่ยง" ผ่านการท่องเที่ยวเชิงนิเวศ บ้านแม่กำปอง อำเภอแม่ออน จังหวัดเชียงใหม่ - สุรีย์วัล เสมอใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study of Transferring Local Wisdom of “Miang” Through Ecotourism, Baan Mae Kampong, Mae On District, Chiang Mai Province aimed at 1) studying and analyzing the development of Transferring Local Wisdom of “Miang” Trough Ecotourism at Baan Mae Kampong 2) studying the potential participation of the community in knowledge management about Transferring Local Wisdom of “Miang” Through Ecotourism at Baan Mae Kampong 3) studying the role of government agencies in promoting and supporting about Transferring Local Wisdom of “Miang” Through Ecotourism at Baan Mae Kampong. The study was a qualitative research. The researcher collected data from individuals concerned about Transferring Local Wisdom of “Miang” through Ecotourism at Baan Mae Kampong. The group consisted of 18 residents who lived in Mae Kampong village such as group of villagers, community leaders, government agencies, and entrepreneurs. The data collection included in-depth interviews, non-participant observation, and the study of documents that were associated. The findings indicated that the form of knowledge management about Transferring Local Wisdom of “Miang” through Ecotourism at Baan Mae Kampong caused by bringing knowledge of occupational tea leaves from their predecessor for a long time which had been cultivated and accumulated until it became a local wisdom that was developed as knowledge base and transferred to the young generations and tourists visited the village. And community context of Mae Kampong village was on the nature of “Kon Paa Miang” (people who lived in the tea forest), so transferring local wisdom was transferred through ecotourism that the village philosophers imparted knowledge to tourists and young people who were interested in learning how to live together with the nature. Inserting content that focused on the conservation of natural resources and the environment coupled with the conservation of tea leaves which went along with the villagers for a long time. Communities leaders and village philosophers were an important person who took part in knowledge management about transferring local wisdom of “Miang” with the accumulated experience of growing tea for a long time by the community leaders attended a key role in raising awareness on the problems and doing activities together which led to the system of knowledge management through various activities about transferring local wisdom of “Miang”. There were also group of entrepreneurs to play a key role in supporting the activities of the village included tourism, marketing, and purchasing the products from locals. Everybody must follow the rules under the supervision of community members. Furthermore, there were government agencies and private sectors had to play their roles in promoting and supporting the form of seminar on the subject as it was realized that the residents would be able to put their knowledge into the potential development of members in community and village. The key recommendations of the study were 1) to create a community model of learning about local wisdom continuance of Miang with comprehensive relay such as Learning Museum 2) should establish relationships to share knowledge with other communities combined with the creation of innovation to disseminate knowledge in a concrete 3) should be extended the cooperation and support from government agencies and private sectors, particularly with local authorities to clear up.